Development of an interactive game-based learning tool to enhance understanding of microbiology in animal health and nutrition - Jennie L. Zambito Ivey; Rachel N. Flinchum; Laney M. Stephens; Phillip R. Myer (Journal of Microbiology & Biology Education)
ABSTRACT Effective science education relies on innovative and engaging teaching tools that enhance student learning and retention. This need is particularly important in agricultural science outreach, where understanding the role of microbiology in animal health and disease is essential for both livestock producers and the public. However, traditional teaching methods often fail to adequately convey complex concepts in an accessible, applicable, and memorable way. To address this gap, a memory-based card game was developed utilizing game-based learning (GBL) principles to improve comprehension of microbiology’s impact on animal health and disease within agricultural systems. This interactive tool balances educational content with gameplay, fostering an engaging learning experience that encourages knowledge retention and real-world application. Through the use of the game, pre- and post-self-assessments indicated learners perceived they were improved in their understanding of microbes in agriculture and noted their greater likelihood to use this information in real-world situations (P < 0.001). By integrating this game into extension and outreach programs, we aim to enhance public understanding of agricultural systems and microbiology’s role in animal health, ultimately improving informed decision-making and agricultural literacy. This approach not only advances microbiology education but also exemplifies the pedagogical benefits of incorporating GBL into agricultural science communication.